Dificuldades na aprendizagem da matemática: um estudo com alunos do ensino médio - Loureiro, Vanilda (2014)
The main objective of this dissertation is to investigate the phenomenon of the difficulty that many high school students have in learning math. For that, it chooses to understand the view of those students about the problem. It discusses somewhat about the influences that the motivation can exert influence in learning. It also discusses ethnomathematics and resolution problems and about the importance that they can achieve during the students’ learning process. Opting for the qualitative research it takes refuge with a questionnaire as a method of gathering information. It points that the students understand that the problem is not just in the teaching method utilized by the teacher or in the abstract nature of mathematics itself. Thus, many of the individuals who contributed to the survey indicate a lack of basic math in elementary school and the need to memorize many formulas and rules as the main reasons for the difficulty of students to learn mathematics in school. As suggestions, the students who completed the questionnaire point mainly to the teacher’s need to change the method of teaching, as well as the use of other resources and / or exploitation of situations of everyday life. It proposes that it is necessary the realization of new studies not only in high school to understand better the problem, but also in elementary school.